The Settlement Structure of the Lower Prekmurje Region in the 17th and 18th Century - Sedar, Klaudija (Anali PAZU HD, 2022)
This article focuses on the south or the lower part of the Prekmurje Region, which as the Prekmurje part of the Bexin Archdeaconry between 1094 and 1777 was under the Diocese of Zagreb. Beside Hungarian parishes, five Slovene parishes belonged to this part: Dolnja Lendava, Turnišče, Dobrovnik, Bogojina and from 1760 on the parish Beltinci. The emphasis is laid on the latter, namely this article is trying to show the settlement situation and the changes occurred through the 17th and 18th century, on the basis of available and accessible sources and writings. Changes definitely took place, as the Prekmurje Region was exposed to certain dangers, like the Turkish invasions and consequently various diseases. In the 18th century, when Turkish invasions stopped, occurred a calmer period with a higher economic, which caused a gradual increase in population.
Keywords: Lower Prekmurje region; settlement; 17th and 18thcentury